1982
DOI: 10.1016/0375-9601(82)90599-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon dispersion relation of gold determined by MOM tunnel structures

Abstract: The dispersion relation of surface plasma oscillations of the Au-vacuum interface was determined from the light emission of Al-Al_03-Au tunnel diodes. The comparison of results with previous data obtained on Ag^indicate that the mechanism of light generation is qualitatively the same for all MOM structures if the anode is one of the noble metals. АННОТАЦИЯДисперсионный закон ПЭВ на разделе золото-вакуум был определён в AI-AI2 O3 -AU туннельных диодах измеряя спектральное и угловое распределения из лучаемого св… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

1982
1982
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
3
0
3
Order By: Relevance
“…These properties, characterizing a 'new type of light' have been broadly studied by many research groups including us, since they offer a broad spectrum of applications in material sciences and nanotechnology [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…These properties, characterizing a 'new type of light' have been broadly studied by many research groups including us, since they offer a broad spectrum of applications in material sciences and nanotechnology [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Signalons enfin que des anomalies peuvent apparaître dans les courbes de dispersion des ondes rayonnées observées expérimentalement, pour des réseaux aux sillons relativement profonds [27,28]. Les Nous avons déterminé ôo à partir de l'intensité 1-1 diffractée dans l'ordre -1 lorsqu'on envoie sur la surface le faisceau d'un laser He-Ne polarisé, d'intensité Io, sous un angle d'incidence 0o.…”
Section: Introductionunclassified
“…Le pic maximum très aigu observé en 03BB ~ 575 nm pour 0 = 0 est dû à l'addition des amplitudes des rayonnements émis par les OPS se propageant en sens inverse sur le réseau, correspondant aux ordres n = ± 1. Les oscillations présentes au voisinage de cette longueur d'onde ont déjà été signalées [28,29] sans être expliquées. L'émission dans l'ordre n = -1 est maximum vers À = 620 nm (hv c2t 2 eV).…”
Section: Introductionunclassified
“…Metal-oxide-metal structures have been investigated as potential light emitting diodes [17,18]. It was shown that the surface between the metal and the dielectric had to be corrugated or roughened in order to excite light emission [23][24][25][26]. Experiments veriÿed the studies.…”
Section: Surface Plasmon Waves Generated By Tunnelling In Metal-insulmentioning
confidence: 98%